1989
DOI: 10.1111/j.1432-1033.1989.tb14620.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of N‐acetyl‐4‐O‐acetylneuraminic‐acid‐containing. N‐linked carbohydrate chains released by peptide‐N4‐(N‐acetyl‐β‐glucosaminyl)asparagine amidase F

Abstract: The carbohydrate chains of equine fibrinogen were enzymatically released by peptide-N4-(N-acetyl-Pglucosaminy1)asparagine amidase F. The oligosaccharides obtained were fractionated by a combination of FPLC and HPLC and analyzed by 500-MHz 'H-NMR spectroscopy. Four monosialo and four disialo diantennary Nacetyllactosamine type of carbohydrate chains occur: 6'5'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 23 publications
5
20
0
Order By: Relevance
“…The 'H-NMR analysis of the mixture of glycopeptides isolated from the pronase digest of Tf2a confirms the presence of NeuSAc and Neu(4,5)Ac2 [23]. Similar 'H-NMR results were obtained for the mixture of glycopeptides isolated from the pronase digest of Tf 4b indicating that in both glyeopeptides Neu5Ac and Neu(4,5)Ac2 are found in the ratio 2: 1.…”
Section: Determination Ofglycan Primary Structuresupporting
confidence: 70%
See 2 more Smart Citations
“…The 'H-NMR analysis of the mixture of glycopeptides isolated from the pronase digest of Tf2a confirms the presence of NeuSAc and Neu(4,5)Ac2 [23]. Similar 'H-NMR results were obtained for the mixture of glycopeptides isolated from the pronase digest of Tf 4b indicating that in both glyeopeptides Neu5Ac and Neu(4,5)Ac2 are found in the ratio 2: 1.…”
Section: Determination Ofglycan Primary Structuresupporting
confidence: 70%
“…Occurrence of this type of sialic acid in horse serum glycoproteins is not new since, in 1968, Pepper [28] has found in horse serum the four following types of sialic acids : NeuSAc, NeuSGc, Ncu(4,5)Ac, and N-glycolyl-4-0-acetylneuraminic acid in the relative ratio 35: 5 : 50: 10, respectively. The presence of Neu(4.5)Ac2 has been determined in horse a,-acid glycoprotein [29], in a,-macroglobulin [30] and in fibrinogen [23]. Concerning the presence of Neu(4,5)Ac2 in horse serotransferrin variants, we have found that it is limited to two of the three analysed variants of Tf 0.…”
Section: Djscussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The N-linked carbohydrate chains were released enzymically from the glycoprotein with PNGase-F [28]. Briefly, a solution of 46 mg K,tu-PA-I in 17 ml 25 mM sodium acetate pH 5.0, diluted to 23.3 ml, containing 30 mM Hepes, 50 m M EDTA, 1 % (by vol.)…”
Section: Liberation Of the N-linked Carbohydrate Chainsmentioning
confidence: 99%
“…The molar ratio of oligosaccharides was determined on basis of absorbance at 205 nm (HPLC on Lichrosorb-NH,) and at 214 nm (FPLC on Mono Q) [28].…”
Section: Isolation Of the Liberated N-linked Carbohydrate Chainsmentioning
confidence: 99%